2018
DOI: 10.7717/peerj.5286
|View full text |Cite
|
Sign up to set email alerts
|

Identifying early decline of daily function and its association with physical function in chronic kidney disease: performance-based and self-reported measures

Abstract: ObjectiveTo verify self-reported basic and instrumental activities of daily living (IADL) with a disability and the results of performance-based tests (namely the Taiwan performance-based IADL (TPIADL), the 2-minute step test (2MST), the 30-second chair-stand test (30-s CST), and handgrip dynamometer measurement) to identify disability early and assess the associations with functional fitness in patients with advanced chronic kidney disease (CKD).MethodsA cross-sectional study of 99 patients with stage 4–5 CKD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…Similarly, a previous cross-sectional study found that muscle strength wasn’t associated with poor performance-based instrumental activities of daily living disability in a population with advanced CKD. 11 Several factors may have contributed to the result. One consideration is that patients with mild-to-moderate CKD may have delayed muscle strength decline in the present study due to farming activities (the present population showed a similar proportion of farmers between those with and without mild-to-moderate CKD; 73.9% versus 73.8%, P = 0.982).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, a previous cross-sectional study found that muscle strength wasn’t associated with poor performance-based instrumental activities of daily living disability in a population with advanced CKD. 11 Several factors may have contributed to the result. One consideration is that patients with mild-to-moderate CKD may have delayed muscle strength decline in the present study due to farming activities (the present population showed a similar proportion of farmers between those with and without mild-to-moderate CKD; 73.9% versus 73.8%, P = 0.982).…”
Section: Discussionmentioning
confidence: 99%
“…10 In contrast, another study found that muscle strength wasn’t associated with poor performance-based instrumental activities of daily living disability in a CKD population. 11 Furthermore, it has been suggested that functional skills are best assessed using gait speed, while some researchers have failed to find an association between slow gait speed and CKD. 12 Therefore, the associations between physical performance and mild-to-moderate CKD require further investigation.…”
Section: Introductionmentioning
confidence: 99%
“…Although performance-based measurements for use in clinical settings are less accurate than laboratory-based tests, they have been shown to be applicable and valuable in detecting impairments at an early stage, before they affect overall physical function and become visible in an ADL index 152 . Performance-based measurements have also been found to be able to discriminate across a larger spectrum of physical fitness and to be capable of measuring changes over time to a greater extent, compared with a self-reported ADL-index 150 .…”
Section: Benefits Of Assessment Of Physical Fitness In Medical In-hosmentioning
confidence: 99%